6-Gingerol prevents MEHP-induced DNA damage in human umbilical vein endothelia cells. (November 2017) - Yang, G; Gao, X; Jiang, L; Sun, X; Liu, X; Chen, M; Yao, X; Sun, Q; Wang, S
Mono (2-ethylhexyl) phthalate (MEHP) is the principal metabolite of di (2-etylhexyl) phthalate, which is widely used as a plasticizer, especially in medical devices. MEHP has toxic effects on cardiovascular system. The aim of this study was to investigate the possibility that 6-gingerol may inhibit the oxidative DNA damage of MEHP in human umbilical vein endothelial cells (HUVECs) and the potential mechanism. The comet assay was used to monitor DNA strand breaks. We have shown that 6-gingerol significantly reduced the DNA strand breaks caused by MEHP. MEHP increased the levels of reactive oxygen species and malondialdehyde, decreased the level of glutathione and activity of superoxide dismutase, and altered the mitochondrial membrane potential. In addition, DNA damage-associated proteins (p53 and p-Chk2 (T68)) were significantly increased by the treatment of MEHP. Those effects can all be protected by 6-gingerol. The results firmly indicate that 6-gingerol may have a strong protective ability against the DNA damage caused by MEHP in HUVECs, and the mechanism may relate to the antioxidant activity.